The Influence of Students' Perception of Social Media and Learning Motivation on Their English Learning - Cadatty, Bethan; Suryadi, Suryadi; Iryani, Endang (Universitas Teuku Umar, 2025)
This study explores the influence of students’ perception of social media and their learning motivation on English learning. As social media becomes increasingly prevalent in students’ daily lives, its role in education, especially language learning, deserves critical attention. This research aimed to examine how students perceive the use of social media in their learning process and how their motivation affects their English learning outcomes. A quantitative survey method was employed, involving 100 eighth-grade students from SMPN 10 Kota Serang. Data were collected through a questionnaire containing 30 items related to the three main variables: students’ perception of social media, learning motivation, and English learning. The findings indicate that both students’ perception of social media and learning motivation significantly influence their English learning. Students who have a positive perception of social media tend to show higher learning motivation, which contributes to better performance in English. These results suggest that the use of interactive digital platforms could enhance students’ engagement and learning outcomes in English education. Further research is recommended to explore the long-term impact of social media integration in language learning.